Development of Hospital Data Warehouse for Cost Analysis of DPC Based on Medical Costs - Muranaga, F.; Kumamoto, I.; Uto, Y. (Methods of Information in Medicine, 2007)
Objectives: To develop a data warehouse system for cost analysis, based on the categories of the diagnosis procedure combination (DPC) system, in which medical costs were estimated by DPC category and factors influencing the balance between costs and fees.Methods: We developed a data warehouse system for cost analysis using data from the hospital central data warehouse system. The balance data of patients who were discharged from Kagoshima University Hospital from April 2003 to March 2005 were determined in terms of medical procedure, cost per day and patient admission in order to conduct a drill-down analysis. To evaluate this system, we analyzed cash flow by DPC category of patients who were categorized as having malignanttumors andwhose DPC category was reevaluated in 2004.Results: The percentages of medical expenses were highest in patients with acute leukemia, non-Hodgkin's lymphoma, and particularly in patients with malignant tumors of the liver and intrahepatic bile duct. Imaging tests degraded the percentages of medical expenses in Kagoshima University Hospital.Conclusions: These results suggested that cost analysis by patient is important for hospital administration in the inclusive evaluation system using a case-mix index such as DPC.
Keywords: DRGs; cost analysis; databases